The Role of Glycocalyx and Caveolae in Vascular Homeostasis and Diseases - Potje, Simone Regina; Paula, Tiago Dal-Cin; Paulo, Michele; Bendhack, Lusiane Maria (Frontiers in Physiology, 2021)
This review highlights recent findings about the role that endothelial glycocalyx and caveolae play in vascular homeostasis. We describe the structure, synthesis, and function of glycocalyx and caveolae in vascular cells under physiological and pathophysiological conditions. In addition, we cite which alterations in glycocalyx and caveolae are associated with impaired production of nitric oxide and generation of reactive oxygen species. Such alterations could contribute to the development of vascular diseases, atherosclerosis, and hypertension.